The impact of green finance, renewable energy, and economic growth on energy transition in African countries - Malatji, Charity Tumisho (Graduate School of Business (GSB), 2025)
Energy transition demands radical and immediate action, requiring substantial mobilisation of green finance to advance progress towards limiting global warming to 1.5°C. The impact of green finance, renewable energy, and economic growth on carbon dioxide emissions has been assessed, however, limited to developed countries and China. The study poses the question whether green finance, renewable energy, and economic growth have an impact on carbon dioxide emissions in selected African countries. The study employed a panel PMG-ARDL approach, over the period 2000 – 2019. The findings indicate that in the long run, renewable energy has a negative impact on carbon dioxide emissions, whereas green finance and economic growth positively impact carbon dioxide emissions. Moreover, in the short run, green finance has a negative impact on carbon dioxide emissions, while renewable energy and economic growth indicate an insignificant impact on carbon dioxide emissions. Lack of access to green finance is the biggest obstacle to Africa's energy transition. The study suggests an improved leadership commitment; and environmental policy implementation to accelerate the energy transition.